Periodic trends in electron transport through extended metal atom chains: comparison of Ru-3(dpa)(4)(NCS)(2) with its first-row analogues - Mohan, P; Georgiev, V; McGrady, J (2012)
Density functional theory is used to reconcile the structural, magnetic and electron transport properties of a triruthenium extended metal atom chain, Ru 3(dpa) 4(NCS) 2. The distinct bending of the Ru-Ru-Ru core in this species is traced to strong second-order mixing between levels of σ and π symmetry that are near degenerate in the linear geometry. The dominant electron transport channel is formed by the LUMO, an orbital of π* symmetry that lies just above the Fermi level of the gold electrode. The bending has a substantial impact on electron transport in that it induces a spin crossover from a quintet to a singlet which in turn brings the LUMO much closer to the Fermi level. The presence of significant net π bonding in the metal chains also broadens the π/π nb/π* manifold, such that the channel is not strongly perturbed by the electric field, even at a bias of 1.0 V. The presence of a robust π symmetry conduction channel marks the triruthenium systems out as quite distinct from its first-row counterparts, Cr 3(dpa) 4(NCS) 2 and Co 3(dpa) 4(NCS) 2, where current flows primarily through the σ framework. This journal is © 2012 The Royal Society of Chemistry.